Development of High-SPF Sunscreen Cream Formulation Using Green Tea (Camellia sinensis L.) Extract Obtained via Combined Pulsed Electric Field and Microwave–Ultrasound Assisted Extraction (PEF-MUAE) - Yulianti, Eny; Warsito; Akhmad Sabarudin; Bayyinatul Muchtarohmah; Titian Ajeng Wahyuningtyas; Okky Vara Velya (The Journal of Pure and Applied Chemistry Research, 2025)
The tea plant (Camellia sinensis L.) is renowned for its medicinal benefits, largely attributed to its secondary metabolites, which demonstrate significant antioxidant potential. This study focused on evaluating the antioxidant activity of green tea extract and determining the Sun Protection Factor (SPF) of sunscreen formulations containing the extract. The green tea was extracted using a combined Pulsed Electric Field- Microwave-Ultrasonic Assisted Extraction (PEF-MUAE) with distilled water as the solvent. The obtained extract underwent phytochemical analysis and SPF assessment. Various sunscreen formulations were tested for washability, total phenolic content, antioxidant activity, and SPF. The antioxidant activity and total phenolic content of the cream were measured using UV-Vis spectrophotometry, while SPF values were determined with UV-DRS spectrophotometry. The first formulation (F0) consisted of only the cream base, made without green tea extract or TiO₂. The second formulation (F1) was made with TiO₂ but without the extract. The third formulation (F2) contained the extract without TiO₂. Finally, the last formulation (F3) included both green tea extract and TiO₂. The extraction method produced a yield of 38.8%, with all cream formulations exhibiting ease of washability. The antioxidant activity of F0, F1, F2, and F3 was measured at 30.977, 32.866, 34.661, and 28.172 ppm. The total phenolic content and SPF values for the various cream formulations (F0, F1, F2, and F3) were 156.506 ± 10.824, 266.391 ± 33.760, 604.978 ± 22.815, and 680.873 ± 25.881 mg GAE/g for total phenolics, and 14.647, 22.656, 55.136, and 62.935 for SPF values.